Kinetics of inflammation- and hypoxia-related miRNAs and association with neurological outcomes in survivors of out-of-hospital cardiac arrest. (3rd May 2023) - Jimenez Trinidad, F; Moreno, E; Roca, C; De Diego, O; Lopez, T; Izquierdo, M; Tercero, A; Gaig, C; Dantas, A; Andrea, R
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Saludo Carlos III (ISCIII)-FEDER PI19/00264 Ministerio de Universidades - FPU19/04925 Background: Inflammation and hypoxia are key players in the pathophysiology of Out-of-Hospital Cardiac Arrest (OHCA), and may be directly associated with neurological outcomes (NO). MicroRNAs that control inflammation (inflam-miRNAs) and hypoxia (hypoxi-miRNAs) have been largely associated with cardiovascular and neurological diseases. However, the kinetics and regulatory role of inflam- and hypoxi-miRNAs on NO in OHCA have been poorly studied. Purpose: To associate inflam- and hypoxi-miRNA expression kinetics with NO in OHCA survivors. Methods: Consecutive OHCA patients were prospectively recruited from March 2019 to November 2020. Blood samples were taken during hospitalization at 0 and 24 hours after admission. Patients were grouped according to their cerebral performance category (CPC) at hospital discharge. In silico analysis determined miRNAs to be analysed in serum. Results: A total of 40 patients (10% women, age 60 ± 10 years) were analysed. At hospital discharge, 17 patients survived with good NO (GNO; CPC 1-2) and 13 patients presented a poor NO (PNO; CPC 3-5). In silico analysis unveiled a network of 11 miRNAs related to cardiovascular and coronary artery disease as well as hypoxic encephalopathy and neuro-inflammation (Figure 1). At their hospital admission, differences between GNO and PNO patients in anti-inflammatory (AI) miR-181a-5p and pro-inflammatory (PI) miR-155-5p levels were observed (p-value = 0.0355 and 0.0310 respectively) (Figure 2A). However, there were no differences in levels of AI miR-let-7a-5p and PI miR-1-3-p at 0h and 24h between both groups (Figure 2B). When comparing changes in inflam-miRNA expression between 0 and 24 h, PNO patients showed an augmented total inflammatory response (TIR), increasing the levels of a) AI miR-181-5p (p-value = 0.0295) and miR-let-7a-5p (p-value = 0.0013); and b) PI miR-155-5p (p-value = 0.0112) and miR-1-3-p (p-value = 0.0375) (Figure 2C). Changes in inflam-miRNAs in PNO were associated to an increase in blood C-reactive protein levels during hospitalization (GNO 18.73 ± 5.4 mg/L vs. PNO 26.00 ± 10.31 mg/L, p-value = 0.0055). (Figure 2D). In this inflammatory scenario, only GNOP patients were able to increase levels of key ischemia-protective hypoxi-miRNA miR-484 during first 24h (p-value = 0.0301) (Figure 2E). Conclusions: In survivors of OHCA, the kinetic of inflam- and hipoxi-miRNAs expression changes during first 24h hospital admission is correlated with inflammation and NO. GNO Patients have decreased miRNA-mediated changes in TIR and increased miRNA-mediated hypoxic protection while PNO patients have increased miRNA-mediated changes in TIR with reduced miRNA-mediated hypoxic protection. These results focus the importance to contain inflammatory response in OHCA survivors as well as to stimulate mechanisms in front of ischemia, giving relevance to novel miRNA-mediated targetable mechanisms.